Synopsis of shoulder surgery - Srikumaran, Uma (Thieme, 2021)
"Shoulder problems comprise a significant percentage of orthopaedic practice, including trauma and sports related injuries. Synopsis of Shoulder Surgery by Uma Srikumaran and esteemed contributors provides a concise, well-rounded perspective on the surgical and nonsurgical management of a wide array of shoulder disorders. The opening chapters lay a solid foundation of knowledge, covering anatomy, physical examination of the shoulder, surgical approaches to the shoulder, imaging, and the use of diagnostic and therapeutic injections. Subsequent chapters succinctly discuss management of a comprehensive range of shoulder conditions, organized by the underlying type of pathology. The final chapters provide insightful pearls on shoulder rehabilitation and perioperative pain management"--